Electrode material with both electronic conduction and interface adhesion and preparation method thereof
By designing a bicontinuous phase separation structure in the electrode material, the competition between conductivity and adhesion is solved, and the high conductivity and high adhesion are achieved, which significantly improves the application effect of the electrode material.
Patent Information
- Application Number
- CN202510148398.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-11
AI Technical Summary
There is a competitive relationship between conductivity and adhesion of existing electrode materials, which makes it difficult to take into account both high conductivity and high adhesion, resulting in poor application effects in fields such as human-computer interaction and intelligent medical care.
By designing a bicontinuous phase separation polymer material, a submicron bicontinuous phase separation structure is formed by using the solubility difference between the conductive phase and the adhesive phase in the aqueous phase and the organic phase, and a submicron bicontinuous phase separation structure is achieved to achieve a uniform distribution between the conductive phase and the adhesive phase and an internal continuous conductive network.
The balance between the intrinsic electron conductivity of the electrode material between 10-120S/cm and the interface adhesion energy of 200-600J/m2 is achieved, which significantly improves the stability and application effect of the electrode.
Smart Images

Figure CN119798900A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electronic interfaces, and in particular to an electrode material having both electronic conductivity and interface adhesion and a preparation method thereof. Background Art
[0002] At present, electrode materials are used in human-computer interaction and health monitoring, and are used for monitoring physiological electrical signals such as electrocardiogram, electromyography, and electroencephalogram. These scenarios require electrode materials with high conductivity and good adhesion. For example, the monitoring of electrophysiological signals often requires electrode materials to ensure sufficient interface adhesion to prevent motion artifacts and signal drift caused by interface detachment. At the same time, a certain conductivity is also required to reduce interface impedance and obtain signal gain. For example, in electrical stimulation therapy, electrode materials are also required to ensure excellent electrical conductivity to reduce energy consumption, and the interface is also required to be tightly adhered to achieve stable electrical stimulation under dynamic conditions. Therefore, in the context of the era of smart medical care and human-computer interaction, designing an adhesive and conductive electrode material has a high application value.
[0003] However, the adhesion and conductivity of the electrode interface are in a competing relationship. Academician John A. Rogers, one of the pioneers in the field of flexible electronics, developed a composite electrode based on metal and adhesive backing as early as 2019. They found that when the conductive filling decreases, the adhesion increases, and the interface impedance increases; when the conductive filling increases, the interface impedance decreases, but the adhesion weakens. Some researchers also prepare conductive adhesives by mixing conductive fillers (such as carbon nanotubes, silver nanowires, etc.) with adhesives. However, based on the percolation theory, the conductive component needs to reach a certain percolation threshold to obtain better conductivity (<1S / cm), and too high a non-adhesive conductive content will greatly reduce the adhesion performance of the adhesive (<100J / m 2 ). The team led by Zhou Xuechang of Shenzhen University used a conductive polymer poly (3,4-ethylenedioxythiophene): polybenzenesulfonic acid and a supramolecular polyvinyl alcohol material to prepare a conductive adhesive with good mechanical properties. However, the clustering of the conductive polymer caused this type of design to face the incompatibility between adhesion and conductivity (maintaining 120 J / m at 10 S / cm). 2 skin interface adhesion energy).
[0004] The competitive relationship between conductivity and adhesion comes from the competition between the two properties for the effective area on the interface. If the competition between the two materials on the interface can be balanced, compatible interface conductivity and adhesion can be obtained. In addition, the conductive phase also needs to be effectively internally penetrated and interconnected to obtain overall good conductivity. Therefore, how to design an electrode material that takes into account both conductivity and adhesion is one of the solutions to the current unstable problem of electrode-tissue adhesion.
[0005] In polymer research, there is a micro-region bicontinuous phase separation structure, that is, two polymers each form a continuous phase that penetrates each other. This structure can form a uniform two-phase distribution at the interface, while the internal polymers also maintain effective penetration. Therefore, the present invention will solve the current unstable problem of electrode-biological tissue adhesion by designing a bicontinuous phase separation polymer material, and finally designing an electrode material and its preparation method that take into account both conductivity and adhesion. Summary of the invention
[0006] In view of this, in order to obtain an electrode material that takes into account both conductivity and adhesion, according to the micro-region bicontinuous phase separation structure in polymer research, that is, two polymers each form a continuous phase that penetrates each other, this structure can form a uniform two-phase distribution on the interface, and at the same time the internal polymers also maintain effective penetration. The purpose of the present invention is to provide an electrode material with both electronic conductivity and interface adhesion and a preparation method thereof. The electrode material is a microscopic bicontinuous phase separation structure of a conductive phase and an adhesive phase, and ultimately a uniform distribution of the conductive phase and the adhesive phase on the surface interface is obtained, and the internal continuous conductive network can make the material have excellent electronic conductivity. The electrode material that takes into account both conductivity and adhesion can be used for applications such as physiological electrical signal acquisition, epidermal or neural electrical stimulation, and is one of the most important basic materials in the fields of human-computer interaction, intelligent medical care, etc.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] In the first aspect, the present invention provides an electrode material having both electronic conductivity and interface adhesion, wherein the electrode material comprises a conductive phase and an adhesive phase; the conductive phase is dispersed in an aqueous phase, the adhesive phase is dispersed in an organic phase, and the conductive phase and the adhesive phase form a submicron bicontinuous phase separation structure through phase separation, thereby achieving a reasonable distribution of the two phases at the interface.
[0009] The present invention utilizes the difference in solubility of the conductive phase and the adhesive phase in the aqueous phase and the organic phase, and a spontaneous phase separation process occurs in the mixed phase of the aqueous phase and the organic phase to form a microscopic interpenetrating structure. After drying, the conductive phase and the adhesive phase can be reasonably distributed at a submicron scale. The final material exhibits an intrinsic electronic conductivity of 10-120S / cm and exhibits excellent adhesion, such as 200-600J / m 2 The electrode material with both electronic conductivity and interface adhesion obtained by the present invention can be used as an interface material for skin electrodes, and is used for applications such as stable enhancement of electrophysiological monitoring signals and electrical stimulation efficiency.
[0010] As a further embodiment of the present invention, the conductive phase is a conductive polymer that is water-dispersible and soluble in water and has good electronic conductivity.
[0011] As a further solution of the present invention, the conductive phase is 3,4-ethylenedioxythiophene: polyphenylsulfonic acid (PEDOT:PSS) as a base material, and is compounded with any one or more combinations of conductive nanoparticles, nanowires, water-dispersible graphene, and carbon nanotubes to prepare a water-phase dispersed material.
[0012] As a further solution of the present invention, the adhesive phase has intrinsic interfacial adhesion performance, and the adhesive phase is any one or more combinations of polyacrylate, acrylic acid-acrylate copolymer, and waterborne polyurethane.
[0013] As a further embodiment of the present invention, the adhesive phase is dissolved by a low boiling point organic solvent, and the low boiling point organic solvent is ethanol, methanol or acetone which is miscible with water.
[0014] As a further scheme of the present invention, when the conductive phase and the adhesive phase form a submicron bicontinuous phase separation structure through phase separation, the conductive phase is dispersed in the aqueous phase and the adhesive phase is dispersed in the organic phase, and then the conductive phase is added to the adhesive phase system at a solid content ratio of 1%-10%, and the mass ratio of the conductive phase to the adhesive phase is 1:1 to 10:1, and dynamic mixing is performed to obtain a uniform two-phase dispersed system.
[0015] As a further solution of the present invention, when performing dynamic mixing, one or more methods of stirring and shearing are used for dynamic mixing.
[0016] As a further solution of the present invention, the electrode material having both electronic conductivity and interface adhesion also includes adding a small molecule plasticizer or polar substance with an overall solid content of 0.1%-10% to adjust the conductivity. The small molecule plasticizer or polar substance is a mixed system of one or more of dimethyl sulfoxide, ethylene glycol, and ionic liquid. Through the mixed system of small molecule plasticizers or polar substances, the conductivity of the electrode material can be effectively optimized and good adhesion can be maintained.
[0017] As a further solution of the present invention, the electrode material having both electronic conductivity and interface adhesion also includes adjusting the conductivity and adhesion properties through annealing heat treatment. Annealing can help adjust the distribution state of the conductive phase and the adhesion phase and enhance the overall performance of the material.
[0018] As a further solution of the present invention, the electrode material having both electronic conductivity and interface adhesion can be processed by laser cutting, liquid printing, etc., and adhered to the surface of other materials to form a multilayer structure. This electrode material is different from other electrode materials that are conductive but not adherent or adherent but not conductive. This electrode material can achieve a high adhesion ability while achieving an intrinsic conductivity of 10-120S / cm, such as >200J / m 2 .
[0019] In a second aspect, the present invention further provides a method for preparing an electrode material having both electronic conductivity and interface adhesion, comprising the following steps:
[0020] Prepare adhesive phase materials: select commercially available adhesive glue or self-synthesized adhesive glue, and obtain adhesive phase solution through dissolution or polymerization reaction;
[0021] Prepare conductive phase materials: select conductive polymers and mix with small molecule plasticizers, polar substances or water, adjust conductivity, and obtain conductive phase solutions;
[0022] The adhesive phase solution and the conductive phase solution are mixed in proportion until the overall solution becomes a bluish-white uniform dispersion to form a phase-separated mixed solution;
[0023] The mixed solution is poured into a mold, dried and annealed to obtain a conductive adhesive electrode with electronic conductivity and interface adhesion.
[0024] As a further embodiment of the present invention, the method for preparing the electrode material having both electronic conductivity and interface adhesion also includes: processing the electrode material into a desired shape, or adhering it to other substrate surfaces to form a multilayer structure or applying it to the skin surface.
[0025] As a further solution of the present invention, the adhesive phase material is polyacrylate adhesive glue, polyurethane glue, or self-synthesized polyacrylic acid-isobornyl acrylate.
[0026] As a further solution of the present invention, the solid content concentration of the adhesive phase solution is 3%-20%.
[0027] As a further solution of the present invention, the conductive phase material is a conductive polymer PEDOT:PSS, and a small molecule plasticizer is added to mix with the conductive polymer to adjust the conductivity.
[0028] As a further embodiment of the present invention, the mass ratio of the PEDOT:PSS to the small molecule plasticizer is 20:1 to 30:1.
[0029] As a further solution of the present invention, the temperature of the annealing process is 100-110° C. and the duration is 5-20 minutes.
[0030] As a further solution of the present invention, the electrode material can be shaped by laser cutting, liquid printing or extrusion printing, and the electrode material can be applied to skin electrodes, wearable electronic devices, electrophysiological monitoring, artificial electronic skin and other fields.
[0031] In the above technical scheme, the present invention provides an electrode material having both electronic conductivity and interface adhesion and a preparation method thereof, and the beneficial effects are:
[0032] The electrode material provided by the present invention realizes the micro-nanostructure distribution of the microscopic conductive phase and the adhesive phase by utilizing the solubility difference of the polymer in water and organic solvents and the spontaneously formed phase separation process; secondly, the two phases prepared by this method are continuous and uniform, and there is no need to consider the conductive filling characteristics that require too high a percolation threshold, and a higher electronic conductivity can be achieved at a lower conductive phase content; finally, the material can simultaneously exhibit high electronic conductivity (conductivity should be >10S / cm) and high adhesion (adhesion to the skin interface can reach >200J / m 2 ), which is unmatched by traditional electrode materials.
[0033] These and other aspects of the present invention will be more clearly understood in the following description of the embodiments. It should be understood that the above general description and the following detailed description are only exemplary and explanatory and cannot limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.
[0035] Figure 1 Schematic diagram of the principle of an electrode material having both electronic conductivity and interface adhesion according to an embodiment of the present invention.
[0036] Figure 2 This is a structural diagram of a phase separation model in an electrode material having both electronic conductivity and interface adhesion according to an embodiment of the present invention.
[0037] Figure 3 This is a transmission electron microscopy characterization result diagram of phase separation in an electrode material having both electronic conductivity and interface adhesion according to an embodiment of the present invention.
[0038] Figure 4 This is a diagram showing the atomic force microscopy characterization results of phase separation conduction in an electrode material having both electronic conductivity and interface adhesion according to an embodiment of the present invention.
[0039] Figure 5 The following is a picture of the phase-separated conductive adhesive prepared by the present invention and a schematic diagram of the state of being adhered to the surface of the skin.
[0040] Figure 6 It is a schematic diagram showing the change of conductivity with the conductive phase content in the phase separation conductive adhesive of the present invention.
[0041] Figure 7 This is a comparison chart showing the change in interfacial adhesion with the conductive phase content in the phase separation conductive adhesive of the present invention.
[0042] Figure 8 This is a comparison chart of the interface impedance test results on the skin of the conductive adhesive prepared by the present invention using a conductive phase with a solid content of 10% and commercial gel electrodes and copper electrodes.
[0043] Fig. 9 This is a photo of the conductive adhesive with a shape prepared by printing in the present invention attached to a release film. DETAILED DESCRIPTION
[0044] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0045] In some of the processes described in the specification and claims of the present invention and the above-mentioned figures, multiple operations that appear in a specific order are included, but it should be clearly understood that these operations may not be executed in the order in which they appear in this article or executed in parallel. The serial numbers of the operations, such as 101, 102, etc., are only used to distinguish different operations, and the serial numbers themselves do not represent any execution order. In addition, these processes may include more or fewer operations, and these operations may be executed in sequence or in parallel. It should be noted that the descriptions of "first", "second", etc. in this article are used to distinguish different messages, devices, modules, etc., do not represent the order of precedence, and do not limit the "first" and "second" to be different types.
[0046] The following will be combined with the drawings in the exemplary embodiments of the present invention to clearly and completely describe the technical solutions in the exemplary embodiments of the present invention. Obviously, the described exemplary embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0047] In order to ensure the conductive adhesion requirements of electrodes in application scenarios such as electrophysiological signal monitoring and electrical stimulation therapy, the present invention proposes an electrode material with both electronic conductivity and adhesion and a preparation method thereof, aiming to achieve high conductivity of the electrode while maintaining high interface adhesion. Figure 1 As shown, the present invention is inspired by the dual continuous phase of materials science. By introducing the basic principle that the conductive phase and the adhesive phase have different solubilities in the aqueous phase and the organic phase, a spontaneous phase separation process during the fusion of the aqueous phase and the organic phase is used to prepare a mutually continuous and interpenetrating micro-nano phase separation structure, which ultimately exhibits higher electrical conductivity and excellent interface adhesion performance.
[0048] The electrode material of the present invention, which has both electronic conductivity and adhesion, greatly reduces the content of high conductive fillers required by traditional conductive fillers that rely on percolation thresholds through a dual-continuous phase separation structure, and only requires the addition of less than 10% of a conductive phase to achieve a high conductivity. In addition, the present invention can further improve the conductivity by introducing some small molecule plasticizers, such as dimethyl sulfoxide, ionic liquids, etc. When the material is applied to the electrode-skin interface, it exhibits extremely low interfacial impedance and superior properties such as greater charge injection capacity compared to commercial electrodes, showing broad application prospects in the fields of human-computer interaction, smart medical care, etc.
[0049] For details, see Figures 2 to 5 The model diagram and characterization diagram results shown in the figure are as follows. Figures 2 to 4 Based on the microstructure observed by a transmission electron microscope and the surface conductive phase distribution observed by a conductive atomic force microscope, it can be imagined that the conductive adhesive film prepared by the present invention has a two-phase continuous phase separation structure. Figure 5 For the prepared phase separation membrane morphology, it can be seen that the membrane prepared by the present invention has good flexibility and better adhesion on the surface.
[0050] See also Figure 6 and Figure 7 As shown, the conductivity of the phase-separated conductive adhesive can increase from 60S / cm to 120S / cm as the conductive phase increases and the interfacial conductive content increases, but the interfacial adhesion force will decrease from 650N / m to 150N / m. In some embodiments, see Figure 8 As shown, the phase-separated conductive adhesive as a skin electrode can obtain lower interface impedance results compared with commercial gel electrodes and metal copper electrodes.
[0051] See also Fig. 9 As shown, the electrode precursor liquid can be prepared into an adhesive conductive adhesive of a specific shape by printing or other methods.
[0052] The following is a further description of the method for preparing an electrode material having both electronic conductivity and adhesion according to the technical solution of the present invention in conjunction with specific embodiments:
[0053] Example 1
[0054] This embodiment provides an electrode material having both electronic conductivity and adhesion. The electrode material of this embodiment is prepared by the following steps:
[0055] Step S10: Preparation of adhesion phase:
[0056] First, the purchased commercial polyacrylate adhesive solid is dissolved at a solid content of 10%, and ethanol is selected as the solvent. The mixture is stirred and dissolved at 40° C. for later use.
[0057] Step S20: Preparation of conductive phase:
[0058] The purchased conductive polymer solution (PEDOT:PSS aqueous solution with 1% solid content) was mixed with dimethyl sulfoxide, a small molecule plasticizer, and stirred at a mass ratio of 20:1 for PEDOT:PSS solution: dimethyl sulfoxide solution, and set aside.
[0059] Step S30: Phase separation:
[0060] Take 1g of the adhesive phase solution dissolved in the above ethanol and stir rapidly. During the stirring process, add 1g of the conductive phase solution (solid content of the conductive phase is 1%) dropwise. The mass ratio of the conductive phase to the adhesive phase is 1:1, until the whole solution becomes a bluish-white uniform dispersion. Then continue stirring for 10 minutes.
[0061] Step S40: Drying of the phase separation membrane:
[0062] The above solution was poured into a polytetrafluoroethylene mold for natural drying. After waiting for 1 hour, the liquid in the mold was completely dried, and then placed in a 105°C oven for annealing for 10 minutes. After the annealing was completed, the mold was naturally cooled to prepare a conductive adhesive electrode.
[0063] Example 2
[0064] This embodiment provides an electrode material having both electronic conductivity and adhesion. The electrode material of this embodiment is prepared by the following steps:
[0065] Step S10: Preparation of self-synthesized adhesive phase:
[0066] 1g of acrylic acid monomer and 3g of isobornyl acrylate were dissolved in 2g of dimethylformamide, and 0.01g of azobisisobutylcyanide thermal initiator was added. After heating in an oven at 75°C for 24 hours, the polymerized adhesive was taken out, washed with anhydrous ether, and dried to obtain a polyacrylic acid-isobornyl acrylate adhesive material. The polyacrylic acid-isobornyl acrylate adhesive material was dissolved in methanol to form an adhesive organic solution with a solid content concentration of 3%.
[0067] Step S20: Preparation of conductive phase:
[0068] The purchased conductive polymer solution (PEDOT:PSS aqueous solution with 1% solid content) was precursor-mixed with the small molecule ionic liquid 1-carboxymethyl-3-methylimidazolium chloride, and stirred at a mass ratio of 20:1 for PEDOT:PSS solution:1-carboxymethyl-3-methylimidazolium chloride for later use.
[0069] Step S30: Preparation of phase separation gel:
[0070] Take 1g of the adhesive phase solution dissolved in the above ethanol and stir it quickly. During the stirring process, add 1g of the conductive phase solution dropwise (the solid content of the conductive phase to the conductive phase + the adhesive phase is 1%), and the mass ratio of the conductive phase to the adhesive phase is 1:1, until the overall solution becomes a bluish-white uniform dispersion. Continue stirring for 10 minutes. Pour the above solution into a polytetrafluoroethylene mold for natural drying. After waiting for 1 hour, the liquid in the mold is dried and then placed in a 105°C oven for annealing for 10 minutes. After the annealing is completed, cool naturally to prepare a conductive adhesive electrode ( Figure 5 ).
[0071] Example 3
[0072] This embodiment provides an electrode material having both electronic conductivity and adhesion. The electrode material of this embodiment is prepared by the following steps:
[0073] Step S10: Preparation of adhesion phase:
[0074] Firstly, a commercial water-soluble polyurethane adhesive was selected, placed in a 60°C oven to dry to remove water, and the dried solid was redissolved in ethanol.
[0075] Secondly, 1g of acrylic acid monomer and 3g of isobornyl acrylate were dissolved in 2g of dimethylformamide, and 0.01g of azobisisobutylcyanide thermal initiator was added. After heating in an oven at 75°C for 24 hours, the polymerized adhesive was taken out, washed with anhydrous ether and dried to obtain a polyacrylic acid-isobornyl acrylate adhesive solid material.
[0076] Finally, the waterborne polyurethane solid and the polyacrylic acid-isobornyl acrylate solid material were dissolved in ethanol at a mass ratio of 3:1 to form an adhesive organic solution with a solid content concentration of 3%.
[0077] Step S20: Preparation of conductive phase:
[0078] The purchased conductive polymer solution (PEDOT:PSS aqueous solution with 1% solid content) was mixed with ethylene glycol as a precursor, and stirred at a mass ratio of PEDOT:PSS solution:ethylene glycol of 30:1 for later use.
[0079] Step S30: Preparation of phase separation gel:
[0080] Take four portions of 1g of the adhesive phase solution dissolved in the above ethanol and stir rapidly. During the stirring process, add 1g, 1.5g, 2g and 2.5g of the conductive phase solution dropwise to the four solutions respectively to form conductive phase solid contents of 10%, 15%, 20% and 25%, respectively, until the overall solution becomes a bluish-white uniform dispersion. Continue stirring for 10 minutes. Pour the above solutions into polytetrafluoroethylene molds for natural drying. After waiting for 1 hour, the liquid in the mold is dried and then placed in a 105°C oven for annealing for 10 minutes. After the annealing is completed, cool naturally to prepare four conductive adhesive electrodes with different conductive phase contents ( Figure 6 and Figure 7 ).
[0081] Example 4
[0082] This embodiment provides an electrode material having both electronic conductivity and adhesion. The electrode material of this embodiment is prepared by the following steps:
[0083] Step S10: Preparation of adhesion phase:
[0084] Firstly, a commercial water-soluble polyurethane adhesive was selected, placed in a 60°C oven to dry to remove water, and the dried solid was redissolved in ethanol.
[0085] Secondly, 1g of acrylic acid monomer and 3g of isobornyl acrylate were dissolved in 2g of dimethylformamide, and 0.01g of azobisisobutylcyanide thermal initiator was added. After heating in an oven at 75°C for 24 hours, the polymerized adhesive was taken out, washed with anhydrous ether and dried to obtain a polyacrylic acid-isobornyl acrylate adhesive solid material.
[0086] Finally, the waterborne polyurethane solid and the polyacrylic acid-isobornyl acrylate solid material were dissolved in ethanol at a mass ratio of 3:1 to form an adhesive organic solution with a solid content concentration of 20%.
[0087] Step S20: Preparation of conductive phase:
[0088] The purchased conductive polymer PEDOT:PSS solid was dispersed with water, and a high-speed shearing machine was used to disperse PEDOT:PSS in water to form a high-concentration conductive phase with a concentration of 5%, which was set aside.
[0089] Step S30: Preparation of phase separation gel:
[0090] Take 10g of the adhesive phase solution dissolved in the above ethanol and stir it at high speed. During the stirring process, add 0.4g of the conductive phase solution dropwise (the solid content of the conductive phase to the conductive phase + the adhesive phase is 1%), and the mass ratio of the conductive phase to the adhesive phase is 10:1, until the overall solution becomes a bluish-white high-concentration dispersion. Squeeze the above solution into the extrusion syringe, and use the extrusion printing method to draw an adhesive electrode with a certain shape on the release film. The extruded material is preliminarily dried at 60°C, and then annealed at 105°C.
[0091] The electrode material provided by the present invention realizes the micro-nanostructure distribution of the microscopic conductive phase and the adhesive phase by utilizing the solubility difference of the polymer in water and organic solvents and the spontaneously formed phase separation process; secondly, the two phases prepared by this method are continuous and uniform, and there is no need to consider the excessively high conductive filling characteristics required by the percolation threshold, and a higher electronic conductivity can be achieved at a lower conductive phase content; finally, the material can simultaneously exhibit high electronic conductivity (conductivity should be >10S / cm) and high adhesion (adhesion to the skin interface can reach >200J / m 2 ), which is unmatched by traditional electrode materials.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrode material having both electronic conductivity and interface adhesion, characterized in that: The electrode material comprises a conductive phase and an adhesive phase; the conductive phase is dispersed in an aqueous phase, the adhesive phase is dispersed in an organic phase, and the conductive phase and the adhesive phase form a submicron dual-continuous phase separation structure through phase separation.
2. The electrode material having both electronic conductivity and interface adhesion according to claim 1, characterized in that: The conductive phase is a conductive polymer that has water-phase dispersibility and is soluble in water.
3. The electrode material having both electronic conductivity and interface adhesion according to claim 2, characterized in that: The conductive phase is 3,4-ethylenedioxythiophene: polybenzenesulfonic acid as a basic material, and is compounded with any one or more combinations of conductive nanoparticles, nanowires, water-dispersible graphene, and carbon nanotubes to prepare a water-phase dispersed material.
4. The electrode material having both electronic conductivity and interface adhesion according to claim 1, characterized in that: The adhesive phase has intrinsic interfacial adhesion performance, and the adhesive phase is any one or more combinations of polyacrylate, acrylic acid-acrylate copolymer, and waterborne polyurethane.
5. The electrode material having both electronic conductivity and interface adhesion according to claim 4, characterized in that: The adhesive phase is dissolved by a low boiling point organic solvent, and the low boiling point organic solvent is ethanol, methanol or acetone which is miscible with water.
6. The electrode material having both electronic conductivity and interface adhesion according to claim 1, characterized in that: When the conductive phase and the adhesive phase form a submicron bicontinuous phase separation structure through phase separation, the conductive phase is dispersed in the aqueous phase and the adhesive phase is dispersed in the organic phase, and then the conductive phase is added to the adhesive phase system at a solid content ratio of 1%-10%, and the mass ratio of the conductive phase to the adhesive phase is 1:1 to 10:1, and dynamic mixing is performed to obtain a uniform two-phase dispersed system.
7. An electrode material having both electronic conductivity and interface adhesion according to any one of claims 1 to 6, characterized in that: The electrode material having both electronic conductivity and interface adhesion also includes adding a small molecule plasticizer or polar substance with a total solid content of 0.1%-10% to adjust the conductivity. The small molecule plasticizer or polar substance is a mixed system of one or more of dimethyl sulfoxide, ethylene glycol, and ionic liquid.
8. An electrode material having both electronic conductivity and interface adhesion according to any one of claims 1 to 6, characterized in that: The electrode material having both electronic conductivity and interface adhesion also includes adjusting the conductivity and adhesion performance by annealing heat treatment.
9. The electrode material having both electronic conductivity and interface adhesion according to claim 7, characterized in that: The conductivity of the electrode material is in the range of 10-120S / cm, and the interfacial peeling energy with the skin is >200J / m 2 .
10. A method for preparing an electrode material having both electronic conductivity and interface adhesion, characterized in that: For preparing the electrode material having both electronic conductivity and interface adhesion as claimed in any one of claims 1 to 9, the preparation method of the electrode material comprises the following steps: Prepare adhesive phase materials: select commercially available adhesive glue or self-synthesized adhesive glue, and obtain adhesive phase solution through dissolution or polymerization reaction; Prepare conductive phase materials: select conductive polymers and mix with small molecule plasticizers, polar substances or water, adjust conductivity, and obtain conductive phase solutions; The adhesive phase solution and the conductive phase solution are mixed in proportion until the overall solution becomes a bluish-white uniform dispersion to form a phase-separated mixed solution; The mixed solution is poured into a mold, dried and annealed to obtain a conductive adhesive electrode with electronic conductivity and interface adhesion.
Citation Information
Patent Citations
Transparent self-adhesive conductive hydrogel electrode and preparation method thereof
CN112450937A
Electrification-ionization double-layer structure epidermal electrode and preparation method and application thereof
CN119257601A
Conductive nanomaterials and composites thereof
US20240315629A1
Polymer composites, methods of fabrication and uses thereof
US20240400823A1
Adhesive electrode for biological signal acquisition, electrode strip, biological sensor, and method for manufacturing adhesive electrode for biological signal acquisition
WO2024204664A1